2019
DOI: 10.1016/j.scitotenv.2018.12.248
|View full text |Cite
|
Sign up to set email alerts
|

Comparing probabilistic and statistical methods in landslide susceptibility modeling in Rwanda/Centre-Eastern Africa

Abstract: Application of suitable methods to generate landslide susceptibility maps (LSM) can play a key role in risk management. Rwanda, located in centre-eastern Africa experiences frequent and intense landslides which cause substantial impacts. The main aim of the current study was to effectively generate susceptibility maps through exploring and comparing different statistical and probabilistic models. These included weights of evidence (Wo E), logistic regression (LR), f requency ratio (FR) and statistical index (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…These factors can be natural or man‐made, and they normally inform about what might have led to slope instability in the past. Studies confirmed that landslides could be triggered by similar causes that led to instability in the past (Abella & Van Westen, ; Nsengiyumva et al., ).…”
Section: Methodsmentioning
confidence: 83%
“…These factors can be natural or man‐made, and they normally inform about what might have led to slope instability in the past. Studies confirmed that landslides could be triggered by similar causes that led to instability in the past (Abella & Van Westen, ; Nsengiyumva et al., ).…”
Section: Methodsmentioning
confidence: 83%
“…Overall, 66.8% had a slide depth <10 m and 94.04% were classified as being small to medium-sized (<100 × 104 m 3 ). Since most of the landslides were small enough against the working scale, their location information could be represented as point features [48,49]. Subsequently, the landslide inventory map of the study area was generated by plotting the centroids of those landslides ( Figure 1).…”
Section: Spatial Databasementioning
confidence: 99%
“…At present, there exist different classes of landslides in the literature, ranging from simple to very complex (Cruden and Varnes 1996;Nsengiyumva et al 2019). These include deep-seated, falls, topples, rotational, flows, lateral spreads, complex, shallow and translational landslides among others (Pradhan et al 2011).…”
Section: Introductionmentioning
confidence: 99%